Social Media Affordances of Ephemerality and Permanence: Social Comparison, Self-Esteem, and Body Image Concerns - Donggyu Kim; Soomin Kim (Social Sciences, 2023)
Instagram provides users with different features, including posts and stories. Instagram post stays on the users’ feeds permanently unless the content is deleted. An Instagram story has an ephemeral nature as the uploaded content vanishes after 24 h. Through a survey of 224 respondents, this study explored individuals’ psychological constructs when using different Instagram features. Instagram usage pattern (i.e., use of different features (video, emoji, etc.), categories of content (food, selfie, etc.) that users usually post, reasons for editing photos (slim body, flawless skin, etc.), amount of time to create and upload a post/story), social comparison, self-esteem, and body image concerns based on the user’s perception of ephemerality and permanency were examined. Results demonstrated that the perception of ephemerality on Instagram stories were negatively related to social comparison and body image concerns. In addition, the longer the amount of time the user spent on posting either a post or story on Instagram, the higher the likelihood the user was to socially compare. Overall, the findings align with previous research suggesting that Instagram users who socially compare are likely to have lower self-esteem and higher body image concerns.